Jian-Pi-Yi-Shen Formula Alleviates Chronic Kidney Disease in Two Rat Models by Modulating QPRT/NAD+/SIRT3/Mitochondrial Dynamics Pathway. (13th December 2021) - Liu, Xinhui; Liu, Siqi; Zhang, Bing; Luo, Denggui; Huang, Shiying; Wang, Fochang; Zheng, Lin; Lu, Jiandong; Chen, Jianping; Li, Shunmin
Abstract : Objective . Jian-Pi-Yi-Shen formula (JPYSF) is a traditional Chinese herbal decoction and has been used for treating chronic kidney disease (CKD) in clinics for decades. However, the potential mechanisms have not been fully elucidated. This study was designed to test the efficacy of JPYSF in treating CKD and explore the underlying mechanism. Methods. Two CKD rat models were established by 5/6 nephrectomy (5/6 Nx) and feeding with adenine-containing feed, respectively. The intervention dose of JPYSF was 10.89 g/kg/d by gastric irrigation. Renal function was assessed by serum creatinine (Scr) and blood urea nitrogen (BUN). Periodic acid-Schiff (PAS) and Masson's trichrome staining were used to evaluate renal histopathological changes. The levels of nicotinamide adenine dinucleotide (NAD + ) were measured by using the enzyme-linked immunosorbent assay kit. The proteins expressions of renal fibrosis, quinolinate phosphoribosyltransferase (QPRT), sirtuin 3 (SIRT3), and mitochondrial dynamics were determined and quantified by Western blot analysis. Results. The results show that administration of JPYSF significantly lowered Scr and BUN levels, improved renal tubular atrophy and interstitial fibrosis, and decreased renal extracellular matrix deposition in two CKD rat models. In addition, CKD rats exhibited suppressed QPRT/NAD + /SIRT3 signal, increased mitochondrial fission, and decreased mitochondrial fusion. JPYSF treatment promoted QPRT/NAD + /SIRT3 signal and restored mitochondrial fission/fusion balance. Conclusion. In conclusion, administration of JPYSF effectively alleviated CKD progression in two rat models, which may be related with regulation of the QPRT/NAD + /SIRT3/mitochondrial dynamics pathway.